Imagining against the nation state: radical singularity and transnationalism in Nuruddin Farah’s Maps - Thiruvarangan, M. (Journal of Postcolonial Writing, 2017)
Nuruddin Farah’s Maps deploys cross-ethnic relationships in its imagination of a radical transnational singularity. This article argues that the thoughts and memories of Askar and Misra, the protagonists who form an unconventional family in the narrative, about their selves, corporeality and belonging contribute to the creation of a singular imagination that challenges the divisive nationalisms of the Somalis and Ethiopians.
Keywords: Nuruddin Farah; Singularity; Nationalism; Transnational; Hybridity; Corporeal